The Influence of Social Media on Young Consumers’ Purchase Intention During Global Pandemic - Jian Ai, Yeow; Chew Sze, Cheah; Sook Fern, Yeo; Yu Wan, Cheang (RSF Conference Series: Business, Management and Social Sciences, 2025)
The year 2020 was undoubtedly going down in history as one of the worst years ever due to the Covid-19 pandemic. Many countries around the world were forced to impose a total lockdown, and this situation occurred again in early June 2021 in Malaysia. Many countries were in their 2nd wave or 3rd wave of lockdown, which caused several restrictions such as movement control, the limit of travel or inter-states. Many businesses were affected. Some big corporations were forced to shut down their productions, lay off, and causing huge numbers of unemployment in the country. There were several news reported that Malaysia’s retails faced bad financial losses and even wave a ‘white flag’ campaign to strike for help from the public. However, instead of begging for help, retailers or businesses should adapt to a new channel and accepting to a more sophisticated computerized operation and diversify into electronic (e-retails) or mobile retails (m-retails) via social media. This study aims to study the causes of young consumer purchase intention using social media during the global pandemic. There are five main variables being studied. The five factors, such as perceived ease of use, perceived usefulness, performance expectancy, interactivity, and intention to express empathy, were selected and analyzed using SPSS Software. This study concluded that perceived ease of use, perceived usefulness, and interactivity have a significant relationship with young consumer purchase intention using social media, while performance expectancy and intention to express empathy have not significant relationship with young consumer purchase intention. This study benefits newly operate SMEs or existing SMEs as they can provide better marketing through social media in order to sustain their businesses.